A Review of Baum's Review of Conceptual Foundations of Radical Behaviorism - Moore, J (Society for the Experimental Analysis of Behavior, Inc, 2011)
Baum expressed numerous concerns about my Conceptual Foundations of Radical Behaviorism in his review. If his review were an independent submission and I were an independent referee, I would recommend that his review be rejected and that he be encouraged to revise and resubmit, once he has studied the field a bit more and clarified for himself and journal readers several important matters. I outline two sets of concerns that he might usefully clarify in his revision: (a) the important contributions of B. F. Skinner to a book about radical behaviorism, and (b) the nature of private behavioral events. In particular, the methodological behaviorism inherent in Baum's position needs to be resolved.